Tess of the d'Urbervilles - Hardy, Thomas 1840-1928 (Lahore New Kitab Mahal, 1912)
Tess Durbeyfield is driven by family poverty to claim kinship with the wealthy D'Urbevilles, and meeting her "cousin" Alec proves to be her downfall. When Angel Clare offers her love and salvation, she must choose whether to reveal her past or remain silent in the hope of a peaceful future.
Include Maps
Keywords: England--Wessex -- England